2021
DOI: 10.3390/ijms221910566
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 Axis Plays a Protective Effect in Streptococcus pyogenes Infection through Strengthening of the Innate Immunity

Abstract: Group A Streptococcus (GAS) causes invasive human diseases with the cytokine storm. Interleukin-33 (IL-33)/suppression of tumorigenicity 2 (ST2) axis is known to drive TH2 response, while its effect on GAS infection is unclear. We used an air pouch model to examine the effect of the IL-33/ST2 axis on GAS-induced necrotizing fasciitis. GAS infection induced IL-33 expression in wild-type (WT) C57BL/6 mice, whereas the IL-33- and ST2-knockout mice had higher mortality rates, more severe skin lesions and higher ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…FBXL19 has been demonstrated to target the IL-33-tumorigenicity 2 IL1RL1 axis, selectively mediating the ubiquitination and degradation of IL1RL1 to limit IL-33-induced pulmonary inflammation ( 43 ). The IL-33/IL1RL1 axis plays diverse roles in various infectious diseases, and studies have suggested that it confers a protective effect against Group A Streptococcus infection by enhancing innate immunity ( 48 ). In our study, the interaction between genotypes and the abundance of Streptococcus on the skin showed a significant association with severity of psoriasis for these 3 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…FBXL19 has been demonstrated to target the IL-33-tumorigenicity 2 IL1RL1 axis, selectively mediating the ubiquitination and degradation of IL1RL1 to limit IL-33-induced pulmonary inflammation ( 43 ). The IL-33/IL1RL1 axis plays diverse roles in various infectious diseases, and studies have suggested that it confers a protective effect against Group A Streptococcus infection by enhancing innate immunity ( 48 ). In our study, the interaction between genotypes and the abundance of Streptococcus on the skin showed a significant association with severity of psoriasis for these 3 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 is a chromatin-related nuclear cytokine, which can play a variety of extracellular biological effects in full-length or truncated active forms [ 24 ]. IL-33 is believed to be involved in cytokine storms induced by a variety of pathogens, including influenza virus [ 27 ], Group A Streptococcus (GAS) [ 28 ], LCMV virus [ 25 , 29 ], COVID-19 [ 30 ], and so forth. However, the role of IL-33 in these diseases is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…In mice with Pseudomonas aeruginosa -induced keratitis, IL-33 effectively reduces inflammation by polarizing the macrophage production of anti-inflammatory mediators [ 195 ]. In addition, the IL-33/ST2 axis provides a protective effect against Streptococcus pyogenes infection by enhancing neutrophil migration and bactericidal activity [ 196 ]. In patients infected with HIV or dengue virus, the sST2 levels in sera rise [ 197 , 198 ].…”
Section: Il-33 and Immune-related Diseasesmentioning
confidence: 99%